2021
DOI: 10.3389/fpls.2021.623723
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Polysaccharide Composition of Grafted ‘Liberty’ Watermelon With Reduced Incidence of Hollow Heart Defect

Abstract: Grafting watermelon scions to interspecific squash hybrids has been found to increase fruit firmness. Triploid (seedless) watermelon are prone to hollow heart (HH), an internal fruit disorder characterized by a crack in the placental tissue expanding to a cavity. Although watermelon with lower tissue firmness tend to have a higher HH incidence, associated differences in cell wall polysaccharide composition are unknown. Grafting “Liberty” watermelon to “Carnivor” (interspecific hybrid rootstock, C. moschata × C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…It is very possible that, in our current study, the phyto-hormonal potential of protein hydrolysate biostimulant was masked by the pronounced rootstock effect on pulp firmness. A plethora of studies have identified pulp firmness as the quality trait most frequently and consistently improved by grafting commercial watermelon cultivars onto inter-specific hybrid rootstocks [22,35]. This effect is associated with increased fruit cell density and altered cell wall characteristics, and it is possibly related to the grafting-mediated differentiation of scion gene expression, which encompasses the over-regulation of cytokine and other metabolites of primary and secondary metabolism [36][37][38][39].…”
Section: Fruit Pulp Texture and Rind Thicknessmentioning
confidence: 99%
“…It is very possible that, in our current study, the phyto-hormonal potential of protein hydrolysate biostimulant was masked by the pronounced rootstock effect on pulp firmness. A plethora of studies have identified pulp firmness as the quality trait most frequently and consistently improved by grafting commercial watermelon cultivars onto inter-specific hybrid rootstocks [22,35]. This effect is associated with increased fruit cell density and altered cell wall characteristics, and it is possibly related to the grafting-mediated differentiation of scion gene expression, which encompasses the over-regulation of cytokine and other metabolites of primary and secondary metabolism [36][37][38][39].…”
Section: Fruit Pulp Texture and Rind Thicknessmentioning
confidence: 99%
“…Determining composition via linkage assembly offers a means to identify the primary cell wall polysaccharides using linkage residue data. , The plant cell wall is composed of a load-bearing network with cross-linking interactions via covalent and noncovalent contacts among sugar linkage residues. Elucidating the physical cross-linking allows for the development of cell wall models and determination of polysaccharide classes .…”
Section: Resultsmentioning
confidence: 99%
“…All samples and sugar standards were injected into an Agilent 7890A GC coupled to a 5975C VL MSD mass spectrometer (Agilent, Santa Clara, CA). GC-MS system and injection methods followed Trandel et al and Pettolino et al , Data were integrated/quantitated via a 5975C Data Analysis MSD Chemstation (Agilent, Santa Clara, CA). Neutral sugars, galacturonic and glucuronic acids, and the degree of methylation (%methylation) were estimated following Pettolino et al To calculate %methylation, the single and double deuterated galactose peak areas of m / z = 117 were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dextran is a kind of branched dextran polymer with molecular weight ranging from 1 kDa to 2000 kDa. The side chain degree of dextrose differs according to molecular weight [ 17 ]. The smaller the molecular weight, the lower the side chain degree.…”
Section: Discussionmentioning
confidence: 99%